Common bean cultivars by sowing time interaction in different locations of Minas Gerais State - Ramalho, Magno Antonio Patto; Abreu, Ângela de Fátima Barbosa; Righetto, Geraldo Umberto (Pesquisa Agropecuaria Brasileira, 1993)
Cultivar x environment interaction was estimated from experiments carried out in sixteen environments including two local ones in 1989 and 1990 and two sowing times in the "drought" season (February and March) and "winter" season (July and August). In each trial, ten cultivars were evaluated in randomized complete blocks with three replications. For grain yield the effects of local, year, month of sowing, and cultivars contributed to more than fifty percent of the total variation. The interactions including cultivar effects, which are the most important, contributed only slightly (14.0%). Among these interactions cultivar x growing seasons was more important than cultivar x local. These results suggest that further bean cultivars evaluation should be carried out in several growing seasons instead of several local ones. Cultivar Eriparsa was the least productive but the most stable in the unfavorable environments. Cultivar Pintado, which was the most productive, showed responsiveness to improving environments.